2017
DOI: 10.1371/journal.pone.0182050
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and acceptability of rapid HIV oral testing among adults attending an urban public health facility in Kampala, Uganda

Abstract: BackgroundThe prevalence of HIV in Uganda is 7.3%, and yet nearly 40% of people living with HIV are unaware of their status. The current HIV testing policy which is strictly blood-based poses several challenges including: a need for high level laboratory skills, stringent waste disposal needs, and painful sample collection. It is envisaged that introduction of a rapid, painless HIV oral fluid test as a potential alternative is likely to increase the number of people testing. The aim of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…These were non-invasiveness of the test procedure, being painless, ease of use, lack of blood loss, and cost effectiveness. These findings did not differ much from an acceptability study conducted in the general population in Uganda (17), and from other studies conducted elsewhere (11,21). It is feared that blood-based methods can cause blood loss and injury to the body, causing cosmetic concerns for some KP groups such as sex workers.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…These were non-invasiveness of the test procedure, being painless, ease of use, lack of blood loss, and cost effectiveness. These findings did not differ much from an acceptability study conducted in the general population in Uganda (17), and from other studies conducted elsewhere (11,21). It is feared that blood-based methods can cause blood loss and injury to the body, causing cosmetic concerns for some KP groups such as sex workers.…”
Section: Discussionsupporting
confidence: 50%
“…Similarly, another study from Kenya by Mugo et al (16) on the uptake and acceptability of an oral HIVST among pharmacy clients showed a high level (84%) of uptake of the test. Another related study conducted in Uganda to determine the accuracy and acceptability of rapid HIV oral testing revealed a rate of acceptability of 87% among 440 clients attending an urban health facility in Kampala (17). As these studies were conducted from a similar setting, they are likely to offer some understanding on the acceptability of oral HIVST in the Ugandan context.…”
Section: Acceptability Of Hivstmentioning
confidence: 98%
“…To address this gap, we advocate strengthening HIV testing campaigns in secondary schools as well as increasing school-based educational programs. The use of urinary or saliva rapid HIV tests can be promoted as they are associated with HIV testing (28,29). However, a study conducted in the USA has shown that the optimal age for HIV testing adolescents and young adults is 25, and screening at age 18 or younger is a less efficient strategy (11).…”
Section: Discussionmentioning
confidence: 99%
“…Oral fluid collection has also already been shown to be acceptable to a group of children for HCV testing and in adults for HIV testing. Other minimally invasive tests such as dry blood spot finger prick have also been used to identify individuals with HBsAg . Although a simple oral sampling method that needs centralized processing may still be associated with losses to follow‐up, it may prove useful for epidemiological serosurveys.…”
Section: Introductionmentioning
confidence: 99%
“…Other minimally invasive tests such as dry blood spot finger prick have also been used to identify individuals with HBsAg. [26][27][28] Although a simple oral sampling method that needs centralized processing may still be associated with losses to follow-up, it may prove useful for epidemiological serosurveys. Oral fluid has variable sensitivity (78%-100%) and specificity (87%-100%) for the detection of HBsAg and depends on collection devices, population and cut-off values used in immunoassays.…”
Section: Introductionmentioning
confidence: 99%